Imaging the southern sky at 159 MHz using spherical harmonics with the engineering development array 2. (22nd April 2022) - Kriele, Michael A.; Wayth, Randall B.; Bentum, Mark J.; Juswardy, Budi; Trott, Cathryn M.
Abstract: One of the major priorities of international radio astronomy is to study the early universe through the detection of the 21 cm HI line from the epoch of reionisation (EoR). Due to the weak nature of the 21 cm signal, an important part in the detection of the EoR is removing contaminating foregrounds from our observations as they are multiple orders of magnitude brighter. In order to achieve this, sky maps spanning a wide range of frequencies and angular scales are required for calibration and foreground subtraction. Complementing the existing low-frequency sky maps, we have constructed a Southern Sky map through spherical harmonic transit interferometry utilising the Engineering Development Array 2 (EDA2), a Square Kilometre Array (SKA) low-frequency array prototype system. We use the m -mode formalism to create an all-sky map at 159 MHz with an angular resolution of 3 degrees, with data from the EDA2 providing information over +60 degrees to –90 degrees in declination. We also introduce a new method for visualising and quantifying how the baseline distribution of an interferometer maps to the spherical harmonics and discuss how prior information can be used to constrain spherical harmonic components that the interferometer is not sensitive to.